Pemanfaatan Mobile Learning Supervisi Klinis Bagi Guru, Kepala Sekolah dan Pengawas Sekolah di Kecamatan Pulo Gadung Jakarta Timur - Rugaiyah, Rugaiyah; Rosyidi, Unifah; Rahmawati, Desi; Nabilah, Siti; Kustandi, Cecep (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
The pandemic era has brought us to situations where social and physical restrictions are demanded. Therefore, like it or not, school principals and supervisors must change the supervision strategy carried out on their teachers and their target schools. Changing supervision strategy needs to be done because learning is no longer done face-to-face in the classroom but online and through clinical supervision activities. However, the problems found indicate that the implementation of clinical supervision has not been optimal because: (1) principals have not effectively carried out their duties as supervisors, such as monitoring, managing, and collaborating with teachers to improve learning. (2) teachers do not yet have adequate skills in managing classes and improving the learning process. (3) teachers and principals are not accustomed to using clinical supervision mobile learning to assist supervision activities in increasing their professionalism. The training activities include the introduction and use of clinical supervision mobile learning, practical sessions on using clinical supervision mobile learning, and mentoring. The training participants consisted of teachers, school principals, and supervisors. The methods used are socialization, training, and focus group discussions. After the training, participants gained new knowledge about mobile learning clinical supervision training. In addition, participants could practice the stages in utilizing clinical supervision mobile learning. Based on the evaluation results, participants argued that this application is essential and relevant for use during covid 19 pandemic conditions.